2010
DOI: 10.1021/ef101184e
|View full text |Cite
|
Sign up to set email alerts
|

Making Fischer−Tropsch Fuels and Electricity from Coal and Biomass: Performance and Cost Analysis

Abstract: Major challenges posed by crude-oil-derived transportation fuels are high current and prospective oil prices, insecurity of liquid fuel supplies, and climate change risks from the accumulation of fossil fuel CO2 and other greenhouse gases in the atmosphere. One option for addressing these challenges simultaneously involves producing ultraclean synthetic fuels from coal and lignocellulosic biomass with CO2 capture and storage. Detailed process simulations, lifecycle greenhouse gas emissions analyses, and cost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
241
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(246 citation statements)
references
References 10 publications
3
241
1
1
Order By: Relevance
“…Greenhouse emissions from coal gasification are higher than that from biomass gasification [45]. This could be due to the high carbon content and low volatile percentage in coal [14].…”
Section: Environmental Benefitsmentioning
confidence: 95%
See 1 more Smart Citation
“…Greenhouse emissions from coal gasification are higher than that from biomass gasification [45]. This could be due to the high carbon content and low volatile percentage in coal [14].…”
Section: Environmental Benefitsmentioning
confidence: 95%
“…For measuring greenhouse emissions, the GHGI (greenhouse gas emission index) is used, which is defined as the lifecycle greenhouse gas emission associated with the energy products divided by the lifecycle greenhouse gas emissions associated with the fossil-fuel-derived products displaced [45]. In a study conducted to produce electricity and FT (Fisher Tropsch) liquids from coal and biomass, Lui et al [45] found that GHGI was 1.71 for coal gasification which came down to 0.96 when a mixture of 40% biomass-60% coal was used as feedstock. From these results, it can be concluded that using biomass with coal is beneficial for the environment in terms of greenhouse gas emissions.…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Two options to upgrade the syngas produced with the packed bed solar gasifier are, electricity generation (typically in a combined cycle gas turbine system) [23][24][25] and/or the production of synthetic crude oil by a Fischer-Tropsch process [23,[26][27][28][29][30] (see Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…2 On the other hand, because of its non-renewable nature, high consumption rates, and the limited reserves of petroleum, transportation fuels from non-petroleum resources have long been extensively explored. [3][4][5][6][7] Among the available choices, the mixture of carbon monoxide and hydrogen (syngas) derived from other carbon-based resources such as coal, natural gas, and biomass has been proven a versatile platform for the synthesis of liquid fuels and high-value added chemicals. [4][5][6][7] Changing environmental regulations in the U.S and abroad are also a major driving force for the production of ultraclean fuels.…”
Section: Introductionmentioning
confidence: 99%